ByzRev 03.2021.022: Alessandra Bucossi – Anna Calia (eds.), Contra Latinos et adversus Graecos.: The Separation between Rome and Constantinople from the Ninth to the Fifteenth Century (Orientalia Lovaniensia Analecta 286 = Bibliothèque de Byzantion 22). Leuven – Paris – Bristol, CT: Peeters 2020. - Monticini, Francesco (The Byzantine Review, 2021)
Alessandra Bucossi – Anna Calia (eds.), Contra Latinos et adversus Graecos. The Separation between Rome and Constantinople from the Ninth to the Fifteenth Century (Orientalia Lovaniensia Analecta 286 = Bibliothèque de Byzantion 22). Leuven – Paris – Bristol, CT: Peeters 2020. XVI, 586 pp. – ISBN: 978-90-429-3785-7 (€ 110)